Eirene e Atena Studi di politica internazionale in onore di Umberto Gori - Attinà, Fulvio; Bozzo, Luciano; Cesa, Marco; Lucarelli, Sonia (Studi e saggi, 2022)
Umberto Gori is an eminent representative of the first wave of international studies in Italy. Throughout the past decades he has constantly been engaged in a number of research projects - ranging from international organization to the theory of international relations, from strategic studies to forecasting - and has taught not only at the University of Florence but also at many other Italian and foreign institutions. The present collection of essays is meant to celebrate his outstanding career. The contributors are students of his who, in turn, have followed his path in teaching and research, and who acknowledge an intellectual debt to him. The volume is arranged according to three general themes that are consistent with Gori's interests: the competitive and cooperative dimensions of the international system; foreign policy and regional governance; the contemporary international order.